2019
DOI: 10.1016/j.freeradbiomed.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-induced iron dysregulation in the lung

Abstract: Iron is one of the most abundant transition elements and is indispensable for almost all organisms. While the ability of iron to participate in redox chemistry is an essential requirement for participation in a range of vital enzymatic reactions, this same feature of iron also makes it dangerous in the generation of hydroxyl radicals and superoxide anions. Given the high local oxygen tensions in the lung, the regulation of iron acquisition, utilization, and storage therefore becomes vitally important, perhaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 179 publications
(219 reference statements)
3
31
1
Order By: Relevance
“…Although confounding by alcohol use, which is positively correlated with both smoking and ferritin values, might explain in part our findings, the Pfeiffer study, which controlled for alcohol, showed that smoking and alcohol had independent effects on ferritin of comparable magnitude . While the mechanism of how smoking impacts iron homeostasis is under active investigation, ferritin's being an acute‐phase reactant responsive to inflammation, infection, and other stimuli is relevant. A large study of the Danish cohort confirms low‐grade inflammation, as measured by C‐reactive protein, in donors who smoked, were obese, and used oral contraceptives .…”
Section: Discussionsupporting
confidence: 64%
“…Although confounding by alcohol use, which is positively correlated with both smoking and ferritin values, might explain in part our findings, the Pfeiffer study, which controlled for alcohol, showed that smoking and alcohol had independent effects on ferritin of comparable magnitude . While the mechanism of how smoking impacts iron homeostasis is under active investigation, ferritin's being an acute‐phase reactant responsive to inflammation, infection, and other stimuli is relevant. A large study of the Danish cohort confirms low‐grade inflammation, as measured by C‐reactive protein, in donors who smoked, were obese, and used oral contraceptives .…”
Section: Discussionsupporting
confidence: 64%
“…Ferritin is a specialized iron storage protein that regulates body iron homeostasis and reflects iron stores in the body. Ferritin also can become elevated in the presence of oxidative stress and inflammation irrespective of iron status and can contribute to various clinical diseases, especially pulmonary and cardio-metabolic diseases [2,3]. Moreover, decreased lung function is associated with oxidative stress and systemic inflammation [4] and increased risk of insulin resistance, diabetes, and cardiovascular disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, these previous studies were not conducted only in healthy subjects. Recent studies have continuously shown that pulmonary [2] and cardio-metabolic diseases [13][14][15][16][17][18] are a recognized complication of excess iron accumulation, and such patients are prone to poor lung function [2,5]. This suggests that inclusion of patients with clinical disease could distort the magnitude of association between lung function and ferritin.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of iron acquisition, utilization, and storage is fundamental to the correct function of lung epithelial, endothelial, and immune cells 37 . Iron is also crucial for the metabolism and growth of native and pathogenic microbes, including those associated with recurrent infections in COPD such as Haemophilus influenzae and Pseudomonas aeruginosa 38,39 .…”
Section: Discussionmentioning
confidence: 99%